2000
DOI: 10.1006/jmsc.2000.0803
|View full text |Cite
|
Sign up to set email alerts
|

Does the concept of spawning per recruit make sense?

Abstract: Density dependence means that exploited fish populations exhibit earlier maturity, a faster growth rate, increased fecundity and reduced egg size. Here, the consequences of these effects on population dynamics, the estimation of spawning biomass per recruit and associated biological reference points are examined by a simulation model. The model is a self-regenerating model in which the population parameters (age at maturity, growth, fecundity, egg size) vary according to three classes of population abundance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 66 publications
0
9
0
3
Order By: Relevance
“…The compensatory nature of density-dependent growth implies that where the process is significant, yield and biomass responses to changes in exploitation are less pronounced than predicted from conventional dynamic pool models assuming density-independent growth (Beverton & Holt 1957;Rochet 2000). Hence disregarding density-dependent growth would lead to conservative reference points for underexploited stocks, but would give rise to over-optimistic assessments of the effectiveness of conservation measures for overexploited stocks.…”
Section: Discussionmentioning
confidence: 99%
“…The compensatory nature of density-dependent growth implies that where the process is significant, yield and biomass responses to changes in exploitation are less pronounced than predicted from conventional dynamic pool models assuming density-independent growth (Beverton & Holt 1957;Rochet 2000). Hence disregarding density-dependent growth would lead to conservative reference points for underexploited stocks, but would give rise to over-optimistic assessments of the effectiveness of conservation measures for overexploited stocks.…”
Section: Discussionmentioning
confidence: 99%
“…This threshold is typically included in the suite of biological reference points against which stock assessments are compared and is particularly useful in establishing thresholds protective of recruitment overfishing (Goodyear 1989;Murawski et al 2001;Fogarty and Gendron 2004). An important caveat in applying this reference point alone is the lack of inclusion of density-dependent changes in vital rates and recruitment (i.e., stock-recruitment relationships; Rochet 2000). To compute EPR, the value (E) of lifetime egg production under conditions of no exploitation is estimated as:…”
Section: Methodsmentioning
confidence: 99%
“…It is worth pondering whether the wide range of F 30%SPR estimates observed in all models indicate true changes in resilience and, consequently, the need to change BRP when environment change, or whether it mostly indicates uncertainty of the estimate. Rochet (2000) has demonstrated that density dependent mechanisms in the adult population (e.g. growth rate, maturation schedule, fecundity, and egg size) may break down the proportionality between spawning stock biomass and recruitment making spawning per recruit an ambiguous concept.…”
Section: Discussionmentioning
confidence: 99%